Enhancing Electrochemical CO2 Reduction using Ce(Mn, Fe)O2 with La(Sr)Cr(Mn)O3 Cathode for High‐Temperature Solid Oxide Electrolysis Cells. Issue 24 (12th May 2021) - Lee, Seokhee; Kim, Minkyu; Lee, Kang Taek; Irvine, John T. S.; Shin, Tae Ho
Abstract: Robust oxide electrodes with high activity and durability have attracted significant attention as alternatives for Ni‐based cathodes in high‐temperature solid oxide electrolysis cells (SOECs). Noncoking La(Sr)Cr(Mn)O3 (LSCM)‐based oxide cathodes have shown promise as durable ceramic cathodes; however, they suffer from low electrocatalytic activities in electrochemical CO2 reduction. In this study, a dual‐phase composite electrode consisting of LSCM and Ce(Mn, Fe)O2 (CMF) is developed to enhance the electrocatalytic activity of CO2 reduction in SOECs. The developed electrode shows excellent electrolysis performance of 2.64 and 1.22 A cm –2 at 1123 K, when voltages of 1.5 and 1.2 V are applied, respectively, without using any precious metal catalysts. The enhanced electrolysis performance is attributed to increases in electrocatalytic activity and surface oxygen vacancies caused by the CMF, which accelerates CO2 adsorption and results in the subsequent dissociation of the carbonate intermediate in the CO2 reduction. Abstract : An excellent CO2 electrolysis current density of 2.64 A cm –2 at 1.5 V in 1123 K is achieved using Ce(Mn, Fe)O2 mixed with La(Sr)Cr(Mn)O3 and dual composite oxide cathode without any precious catalysts on LaGaO3 ‐based solid oxide electrolysis cells.